2019
DOI: 10.1002/ejoc.201901096
|View full text |Cite
|
Sign up to set email alerts
|

Ni(NHC) Catalyzed Rearrangement of 1‐Acyl‐2‐vinylcyclopropanes: Tackling a Mechanistic Puzzle by Combined Experimental and Computational Studies

Abstract: The Ni(NHC) catalyzed rearrangement of 1‐acyl‐2‐vinylcyclopropanes to the corresponding 4‐acyl‐cyclopent‐1‐enes is highly promising for the synthesis of keto‐functionalized annelated bi‐ and tricyclic subunits of natural products. Therefore, we investigated the catalytic activity of Ni(NHC) complexes in the rearrangement of 1‐acyl‐2‐vinylcyclopropanes with different ring sizes and substitution patterns. Surprising effects regarding substrate scope and stereoselectivity of the Ni(NHC) catalyzed vinylcyclopropan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 106 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…On the other hand, vinylcyclopropanes 135a and 135b with a terminal substituted C=C double bond were obtained in decent yields, but unfortunately reacted only sluggishly to give the bicyclo[3.3.0]octenes 134 (Scheme 35). 90 Computational studies confirmed the experimental results. Note that only endo-vinylcyclopropanes endo-135c and endo-135d were reactive in the Ni catalysis, whereas the exo-vinylcyclopropanes exo-135c and exo-135d remained completely unreactive.…”
Section: Account Synlettsupporting
confidence: 59%
See 2 more Smart Citations
“…On the other hand, vinylcyclopropanes 135a and 135b with a terminal substituted C=C double bond were obtained in decent yields, but unfortunately reacted only sluggishly to give the bicyclo[3.3.0]octenes 134 (Scheme 35). 90 Computational studies confirmed the experimental results. Note that only endo-vinylcyclopropanes endo-135c and endo-135d were reactive in the Ni catalysis, whereas the exo-vinylcyclopropanes exo-135c and exo-135d remained completely unreactive.…”
Section: Account Synlettsupporting
confidence: 59%
“…The most annoying side reaction was the [2,3]-sigmatropic rearrangement, resulting in the formation of -allyl sulfides rather than vinylcyclopropanes. 89,90 Despite these disadvantages this approach delivered the desired vinylcyclopropanes 135 in two steps (Route B, Scheme 34), whereas the corresponding Cu-catalyzed…”
Section: Syn Lettmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have cited additional references within the Supporting Information (Ref. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]).…”
Section: Supporting Informationmentioning
confidence: 99%
“…The authors have cited additional references within the Supporting Information. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]…”
Section: Supporting Informationmentioning
confidence: 99%